Assessing the needs and perspectives of patients with obesity and obstructive sleep apnea syndrome following continuous positive airway pressure therapy to inform health care practice: A focus group study - Rapelli, Giada; Pietrabissa, Giada; Angeli, Licia; Bastoni, Ilaria; Tovaglieri, Ilaria; Fanari, Paolo; Castelnuovo, Gianluca (Frontiers in Psychology, 2022)
Objective: This study aims to investigate the lived experience that inpatients with OSAS and comorbid obesity following CPAP therapy made with the disease and the device, and to identify barriers and facilitators to CPAP use to improve rehabilitation provision and aid disease self-management. Methods: Qualitative research using three focus groups was undertaken with a representative sample of 32 inpatients (37% female) undergoing a 1-month pulmonary rehabilitation program at the IRCSS Istituto Auxologico Italiano San Giuseppe Hospital, Verbania, Italy. The focus groups were tape-recorded and contemporaneous notes were made. The tapes were transcribed verbatim and Interpretative Phenomenological Analysis was used to develop themes. Results. Six main themes were extracted: (1) Living the diagnosis as a shock; (2) You should not sleep on it: the importance of prevention; (3) The adjustment to CPAP; (4) Barriers and facilitators to CPAP use; (5) Being three in a bed; and (6) The relationship with the healthcare system. Conclusions: Results of this study suggest potential avenues for interventions to increase adherence to CPAP – including the provision of information and continued support. Individual counseling providing strategies aimed at helping the person to cope with the emotional problem and relational difficulties associated with the use of CPAP, and at strengthening self-efficacy and self-management skills are also encouraged for optimal care during the rehabilitation program.